Mikroplankton abundance on the northern Patagonian shelf (Argentina) during a MV Prof. Bernardo Houssay cruise in September 2015 - Valeria A Guinder; Urban Tillmann; Bernd Krock; Ana L Delgado; Torben Krohn; John E Garzón Cardona; Katja Metfies; Celeste López Abbate; Ricardo I Silva; Rubén Lara (PANGAEA, 2018)
At each study station, surface water temperature (±0.2°C) and salinity (±0.06) were measured in situ by triplicate readings with a multiparameter probe (Horiba U-10, Japan). Using Niskin bottles, surface water samples were collected for quantification of plankton and estimations of chlorophyll a. For the former, 250 ml were fixed with Lugol extquotesingles solution (1% final concentration) and kept in the dark until analysis under the microscope, while for chlorophyll a, a volume of 200–250 mL was filtrated onboard through filter GF/C and kept at -20°C.